Les fourches patibulaires en France. Un patrimoine judiciaire oublié - Mathieu Vivas (Criminocorpus)
This article aims to prove that gibbets, gallows and patibulary forks have their place in the constitution, conservation and valorisation of a historical judicial patrimony. To this end, it presents the links that people of the past and present have had and still have with hanging structures, the way in which people have perceived and still perceive justice through them. It also analyses this penal patrimony according to different scales of observation (past/present, individual/collective, family/society, private/public, etc.) in terms of heritage, transmission, identity and memory.